SIRT1720 promotes survival of corneal epithelial cells via the P53 pathway: SIRT1720 promotes survival of corneal epithelial cells - Al-Sudani, Basma (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Purpose: The protective role of SRT1720 (SIRT1 activator) against the oxidative stress caused by H2O2 in the corneal cell line was investigated in this study.Methods: Human corneal (2.040 pRSV-T) cell lines were cultured and treated with SRT1720 (as SIRT1 activator) and nicotinamide (NAM, a SIRT1 inhibitor) and incubated with H2O2. The expression level of SIRT1, p53, and acetyl-p53 were measured by western blot. Propidium iodine/annexin V-FITC staining, and flow cytometry was used to evaluate apoptosis. The trypan blue assay was used to assess the morphological modifications that occurred after treatment, Pifithrin-α (PFT-α) was used to inhibit the p53 pathway.Results: Under oxidative stress, SRT1720 caused a reduction in acetyl-p53 expression and increased SIRT1 expression. Under oxidative stress, SRT1720 suppressed apoptosis. In comparison, NAM promoted cell apoptosis under oxidative stress. NAM's destructive effect was removed by PFT-α, a suppressor of the p53 pathway. PFT-α reduced the morphological changes in 2.040 pRSV-T cell lines compared to NAM treatment and inhibited apoptosis.Conclusions: The protective effects of the SIRT1 activator (SRT1720) indicate that H2O2 induces oxidative stress-associated cell damage. The results also encouraged us to consider using SRT1720 to improve corneal safety and reduce the adverse effects of oxidative damage.